RELATIVE BLOOD VOLUME: THE MEANS OF INTRADIALYSIS HYPOTENSION PREVENTION - V. A. Terehov; A. G. Strokov (Вестник трансплантологии и искусственных органов, 2010)
Intravascular volume preservation is the first choice measure for the prevention of intradialysis hypotension. At present there are devices that allow continuous monitoring of relative blood volume (RBV) changes during haemodialysis (HD). The aim of this research was to investigate (i) the regularity of RBV curve during haemo- dialysis and (ii) the efficacy of some measures for intravascular volume preservation. In patients with hyperhydration RBV curves were monotone; in all cases relation RBV/ ultrafiltration volume (UF) did not exceed 2,5%/L. In stable patients the RBV curve was immutable in the course of years. Patients with high RBV/UF ratio (>6%/L) formed a high risk group. In these patients stability of RBV was more im- portant and more useful. Isolated UF did not decrease RBV drop, as well as haemodiafiltration online. Albumin administration allows to decrease RBV/UF ratio. After bolus of hypertonic dextrose solution RBV increased for about half of hour. In patients with acute renal injury RBV monitoring was far from reliability in many cases.